CLOUD COST OPTIMIZATION: STRATEGIES FOR EFFICIENT RESOURCE MANAGEMENT AND INFRASTRUCTURE COST REDUCTION IN MODERN CLOUD ENVIRONMENTS - Leite, Eduardo Teixeira (Revista Sistemática, 2023)
Cloud computing has revolutionized the way businesses manage their infrastructure, offering flexibility, scalability, and cost efficiency. However, as organizations scale their operations on the cloud, the challenge of managing and optimizing cloud expenditures becomes increasingly significant. Unchecked usage of cloud resources can lead to wasted computational power, underutilized services, and inflated infrastructure costs, which directly impact the profitability and sustainability of organizations. This paper explores various techniques for optimizing cloud resource usage and minimizing cloud costs. The first part focuses on resource allocation strategies that aim to ensure workloads are running on the most cost-effective resources available. It discusses the importance of using auto-scaling, right-sizing, and workload distribution to avoid unnecessary overhead and prevent resource wastage. The second part of the paper examines the role of cloud management tools and services that can help monitor, analyze, and predict cloud spending, such as cloud cost management platforms, cost monitoring dashboards, and predictive analytics. The third part delves into the concept of serverless computing and how it can help organizations save costs by only paying for resources when they are actually used. Additionally, this paper investigates the impact of cloud service models (IaaS, PaaS, and SaaS) on cost efficiency, exploring the pros and cons of each model and the scenarios in which they are best utilized. A special focus is placed on multi-cloud and hybrid-cloud environments, where cost optimization requires a more nuanced approach, considering various pricing models across multiple cloud providers. Finally, the paper presents real-world case studies and practical recommendations for implementing effective cloud cost optimization strategies. The aim is to provide organizations with actionable insights to improve their cloud spending efficiency, maximize the value they derive from cloud services, and reduce wasteful practices that can inflate infrastructure costs.